Karakteristik Perjanjian Kerja Waktu Tertentu (PKWT) Bagi Pekerja pada Perusahaan Swasta - Made Rama Wiguna Primantara; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2022)
The process of carrying out globalization will act directly or indirectly for the presence of workers. Globalization, characterized by through state fund transactions, we use international standards and international standards for foreign investors and international standards for foreign investors. One of them is the quality point of production and work procedures. . Based on the above background, as well as the features of business contracts of certain employees of the Urban Finance Agency in Denpasar City, it can be based on its duties and laws. , Denpasar City Financial Asset Management Management Agency Event Event Event Event. The methods used are the source of legal studies, the main enterprise and the source of legal materials with secondary legal materials. The results of this study state that the features of employment contracts use a form of legal contract and are very short and effective in the office of the Financial and Asset Management Agency of Denpasar City. Denpasar City Financial and Asset Management Agency Office has defaults for administrative staff. The sanctions imposed on workers who violate the contents of the employment contract consist of a company reprimand, a reprimand (SP 1), a second reprimand (SP 2), and finally ethics if not good. On the employee side, set a third warning letter (SP 3) about job cuts for employees (layoffs).